GABA-A alpha-5 subunit manipulation of maternal separation-induced anxiety in mice - Sloley, Stephanie S. (Tufts Archival Research Center, 2005)
Rodent models were used to examine the role of alpha-5 subunit containing GABAA receptors in modulating anxiety-like behavior through the maternal separation procedure, a reliable model for eliciting early life stress in rodents (Levine, 1957). In the brief separation procedure, subjects were separated from the dam and tested following subcutaneous injections of 0, 3, 5.6, 10, 17 or 30 mg/kg of the alpha-5 subunit preferential antagonist Xli-093, or injections of 0, 3 or 10 mg/kg of the alpha-5 subunit preferential agonist SH-053-2'F-R-CH3. During testing, the number of ultrasonic vocalizations (USVs) was recorded, as well as locomotor activity and motor coordination. In the long-term separation procedure, subjects underwent timed, daily separations, while control subjects were left undisturbed until weaning. Both groups were tested as adults in an open-field paradigm using the Xli-093 compound. In both experiments, no significant differences were found between any of the dose groups or conditions; however a trend towards a peak in USV production occurring at the 5.6 mg/kg dose of Xli-093 in the brief separation experiment was observed. Further testing is required in order to determine whether modulation of the GABAA alpha-5 subunit has an effect on anxiety-like behavior.